Unresectable Malignant Biliary Obstruction: Treatment by Self-Expandable Biliary Endoprostheses. Issue 3 (1993) - Glättli, Andreas; Stain, Steven C.; Baer, Hans U.; Schweizer, Walter; Triller, Jürgen; Blumgart, Leslie H.
Abstract : The primary goal in the treatment of malignant obstruction is the relief of jaundice. Although operative biliary bypass is a reliable method of palliation, nonoperative palliation may be desirable in selected patients. We report our experience with forty-eight self expandable metallic biliary endoprostheses (Wallstent) percutaneously placed in 35 patients with irresectable malignant biliary obstruction. In twelve patients more than one stent was necessary to bridge the entire length of the biliary stenosis. The obstruction was due to primary tumors in 14 and to lymph node metastases in 12. In nine patients transanastomotic stents were placed after previous bilioenteric anastomosis because of malignant obstruction. Complications occurred in 11 patients (31.4%), and five patients died within 30 days of stent placement (14.3%). The mean stent patency to date of patients discharged is 6.1 months, and the mean survival 7.2 months. Follow up data is available for 29 patients, and excellent palliation was achieved for more than 75% of the survival time in 22 (76%). Seven patients have had documented stent occlusion requiring further intervention (24%). In this selected group of patients, the results of percutaneous self-expandable stents are encouraging. However, our data does not support the initial reports of self-expandable endoprostheses that suggest an improved result compared to conventional plastic stents. A randomized study using either expandable stents as compared to operative biliary enteric bypass is necessary.